Collision between a Pedestrian and Tram - Pilot Experiment - Lopot, F.; Kubový, P.; Jelen, K.; Šorfová, M.; Tlapáková, E.; Rulc, V.; Purš, H.; Ježdík, R.; Svoboda, M. (Manufacturing Technology Journal, 2019)
This article intends to present the first results of a long-term research project, which will result in developing a validated model of a pedestrian for the simulation of crash tests involving tram fronts and, where applicable, the fronts of other urban rail vehicles. The current phase of research includes results of the pilot experiment with a crash-test dummy, and these results supplement the results from simulations, thus demonstrating how important it is to pay special attention to the individual stages of a collision event and how important the localisation of and moulding by an individual tram's front panels are for the nature of the monitored stages. In the first stage, inertia of individual body segments plays a significant role, with the primary contact taking place between the tram's bumper and dummy's thigh. The dummy subsequently " takes the shape" of the tram's front with progressive bumps to shoulders and head following. At that moment, the tram brakes, and the dummy begins to disentangle from the front panel. The friction force between the dummy's soles and the surface of the rail track is very significant for the nature of this second stage of the collision event .The dummy then hits the ground. It is an accelerated fall, and under the given conditions, it is the stage that has the most devastating impact on the dummy. The simulation made shows the way to modify this dangerous stage to be less harmful to a pedestrian involved in a tram collision.
Keywords: tram; pedestrian; crash test; simulation; passive safety; FEM /finite element method/